Molecular Crosstalk Between MYC and HIF in Cancer - Li, Yanping; Sun, Xiao-Xin; Qian, David Z.; Dai, Mu-Shui (Frontiers in Cell and Developmental Biology, 2020)
The transcription factor c-MYC (MYC thereafter) is a global regulator of gene expression. It is overexpressed or deregulated in human cancers of diverse origins and plays a key role in the development of cancers. Hypoxia-inducible factors (HIFs), a central regulator for cells to adapt to low cellular oxygen levels, is also often overexpressed and activated in many human cancers. HIF mediates the primary transcriptional response of a wide range of genes in response to hypoxia. Earlier studies focused on the inhibition of MYC by HIF during hypoxia, when MYC is expressed at physiological level, to help cells survive under low oxygen conditions. Emerging evidence suggests that MYC and HIF also cooperate to promote cancer cell growth and progression. This review will summarize the current understanding of the complex molecular interplay between MYC and HIF.